A STRATEGIC PLAN FOR DEVELOPING THE BANDA ARCHIPELAGO AS AN ECOTOURISM AND ENVIRONMENTAL CONSERVATION AREAS (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2020)
Banda Islands is located in the eastern part of Indonesia. These islands are rich in coral reefs and fish. This archipelago has been designated by the Indonesian Government as a tourist area. However, the Banda Islands are facing several economic, social and environmental problems. This study aims to provide policy input to local governments in the form of a strategic plan to develop the Banda Islands as ecotourism and environmental conservation. The method used is “Ecotourism Opportunity Spectrum” (ECOS) and the “Conservation Measures Partnership" (CMP) model. The results of this study produce five strategic plans: a) The first priority is to create a working forum; b) the second is the integration of tasks between the parties involved; c) the third priority is the regulation for changes in coastal land; d) fourth priority is mapping of fishing and; e) the fifth priority is alternative livelihoods.